Compare and Analysis of N-bit Universal Shift Register using Reversible Logic - Pandimeena R, Annapoorani A, Mohnish K, Thanesh S (International Journal of Control and Automation, 2020)
Reversible logic is one of the famous technologies in this modern era. This technology is very much useful in reducing the power i.e. it is used in the lower power design. This reversible logic technology is very much likely to be applied in Quantum computing, Cryptography and also in communication. While fabrication of reversible memory circuits the foremost necessary component used is shift register in reversible logic. During the proposal, we have a tendency to give economical style of various styles of reversible n–bit Universal shift registers like mistreatment Fredkin Gate, Feynman Gate. We've got additionally printed applicable lemmas let's say completely different objects of the proposed models. We made a comparative analysis of universal shift register of reversible logic in various reversible gates. Reversible gate gates used in this are HNF gate, Modified FRG gates, Feynman and Fredkin Gate. By this analysis, we find that the universal shift register using HNF gate needs the lowest range of reversible gates and non-varying inputs, and also it includes the garbage output of less number and the quantum cost than the other two methods.